Functional approaches to infrared Yang-Mills theory in the Coulomb gauge - Weber, Axel; Pawlowski, Jan M. (Arxiv, 2011)
We present the current status of ongoing efforts to use functional methods, Dyson-Schwinger equations and functional renormalization group equations, for the description of the infrared regime of nonabelian (pure) gauge theories in the Coulomb gauge. In particular, we present a new determination of the color-Coulomb potential with the help of the functional renormalization group that results in an almost linearly rising potential between static color charges at large spatial distances.